Faktor-Faktor yang Berhubungan Dengan Kualitas Tidur Pasien Hemodialisis - Caecilia Debora; Tatik Pujiastuti; Lucilla Suparmi (STIKes Panti Rapih, 2022)
ABSTRACT Background: Hemodialysis is a procedure to filter waste and water from the blood as a substitute for kidney function. One of the problems in hemodialysis patients is sleep disturbance. Sleep disturbances are experienced by at least 50-80% of hemodialysis patients. Sleep disturbance that many hemodialysis patients experience is poor sleep quality. (referensi) found that 90.8% of hemodialysis patients have poor sleep quality which is influenced by various factors. Objective: The purpose of this study is to identify factors related with sleep quality in hemodialysis patients. Methods: A literature review was conducted. The database for this study from PubMed, Science Direct and Google Scholar. Articles were selected using the PRISMA Flowchart according to inclusion and exclusion criteria. Quality assessment of the the article was use a critical appraisal from Law, Stewart, Pollock, Letts, Bosch & Wesstmorland (1998). The results of data analysis are presented in the extraction table. Results: Based on the results of article selection, there were 4 articles. Based on a study from 4 articles, it was found that there were three factors related to sleep quality in hemodialysis patients. Those factor are demographic factors including age and gender, biological factors including nutritional status, metabolic acidosis and lifestyle factors including smoking and alcohol consumption. Conclusion: Factors related to sleep quality in hemodialysis patients are demographic factors, biological factors, acidosis and lifestyle factors. Key words: Sleep disturbance, sleep quality, hemodialysis